PENGEMBANGAN VIDEO PEMBELAJARAN FISIKA PADA MATERI FLUIDA STATIS DI SMA - Ade Hadiati Nuzuliana; Fauzi Bakri; Esmar Budi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The aim of this research is to develop the learning media in the form of learning physics videos on the subject of fluid. This research was conducted as a supporting media innovation in scientific learning. The method which used in this research is a research and development (R&D) methods with steps : (1) study literature, (2) needs analysis, (3) design of learning physics videos, (4) develop the learning physics videos, (5) validation of product, (6) field trial, (7) product revision. The learning video has been through a validation test phase with the percentage of 83% according to the material experts, 84,1% according to the media experts, 90,1% according to physics educators at SMA/SMK which is interpreted as â€œvery goodâ€, and 72% according to learning experts which is interpreted as â€œgoodâ€. Limited test result on physics learners shows the percentage of 86,1%, which indicates the learners interest to watch learning video about the static fluid material developed. There is a rise of the learners results from the pre-test to post-test, from the average of 61,13 iti 87,87 respectively. Based on the results of the validation test, experiment, also pre-test and post-test, it can be concluded that the result of the development of physics learning video hdeas been qualified as a medium of learning for the ten grades in high school in their physics class. Keywords: research and development, instructional media, learning video, static fluid.